The Mayflower and the pilgrims' new world - Philbrick, Nathaniel 1956- (G.P. Putnam's Sons, 2008)
After a journey across the Atlantic, the Mayflower's passengers were saved from destruction with the help of the natives of the Plymouth region. For fifty years, peace was maintained as Pilgrims and Natives worked together. But that trust was broken with the next generation of leaders, and conflict erupted that nearly wiped out English and natives alike